Synergistic Flame Retardant Effects of Expandable Graphite and Ammonium Polyphosphate in Water-Blow Polyurethane Foam - Weiguo Yao; Dongyang Zhang; Yixin Zhang; Tao Fu; Dongbo Guan; Yanli Dou (Advances in Materials Science and Engineering)
In this research, expandable graphite (EG) and ammonium polyphosphate (APP) were incorporated into water-blow semirigid polyurethane foam (SPUF) as flame retardants. The synergistic flame retardant effects of EG with APP in SPUF had been studied by thermogravimetric analysis (TGA), limiting oxygen index (LOI), horizontal burning test, polarizing microscope, and scanning electron microscopy (SEM). The results indicated that APP and EG used together in SPUF could effectively improve the flame retardancy of SPUF. When the EG to APP ratio reached 2 : 1 under the total content of flame retardants was kept constant as 20%, the LOI value was increased by about 51% compared to pure SPUF, 2.9% to SPUF/EG and 16.3% to SPUF/APP. Besides, the residual char was increased up to 27.7% displayed by TG test results. SEM shows that burned residues of EG/APP/SPUF present more compact char and worm-like structure. Furthermore, EG shows negative effect on the mechanical property of SPUF with 21.7% decrease in compression modulus, but the mechanical property can be improved by the addition of appropriate content of APP.